2022
DOI: 10.1109/tuffc.2022.3217993
|View full text |Cite
|
Sign up to set email alerts
|

Grating Lobe Reduction in Plane-Wave Imaging With Angular Compounding Using Subtraction of Coherent Signals

Abstract: Plane wave imaging (PWI) with angular compounding has gained in popularity over recent years because it provides high frame rates and good image properties. However, most linear arrays used in clinical practice have a pitch that is equal to than the wavelength of ultrasound. Hence, the presence of grating lobes is a concern for PWI using multiple transmit angles. The presence of grating lobes produces clutter in images and reduces the ability to observe tissue contrast. Techniques to reduce or eliminate the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The motion-induced shift, however, must be known exactly. Kou et al [36] superimposed the envelope images created by three different apodization schemes in the receive focusing. The envelope detection, however, is nonlinear and removes phase information.…”
Section: Discussionmentioning
confidence: 99%
“…The motion-induced shift, however, must be known exactly. Kou et al [36] superimposed the envelope images created by three different apodization schemes in the receive focusing. The envelope detection, however, is nonlinear and removes phase information.…”
Section: Discussionmentioning
confidence: 99%
“…The resolution improvement is still limited by the input signal SNR and a key parameter in NSI is the DC offset, which controls the mainlobe width of NSI. Recently, Kou et al demonstrated that NSI could also reduce grating lobes, which can significantly suppress image artifacts [25]. An initial study using NSI on ultrafast PD microvessel imaging demonstrated NSI's potential for detecting microvessels with contrast agents [26].…”
mentioning
confidence: 99%